Diagnosis of pulmonary and pleural complications of acute necrotizing pneumonia in children - V.A. Dihtiar; A.A. Halahan; D.M. Lukianenko (Zdorovʹe Rebenka, 2025)
Background. Nowadays, the problem of diagnosis and treatment of purulent destructive diseases of the bronchopulmonary system, as well as their prevention in children, remains relevant, which is associated with a large number of pulmonary and pleural forms and complications of acute necrotizing pneumonia. The purpose of the study was to assess the diagnostic capabilities of ultrasound of pleural cavities and lungs in children with acute necrotizing pneumonia for timely detection of complications and choosing treatment strategy. Materials and methods. Forty-one children with purulent necrotizing pneumonia (PNP) aged 1 to 18 years (median age of 8.5 (5; 14) years) underwent inpatient treatment at the CE “Dnipropetrovsk Regional Medical Center of Family Health”. All patients were divided into two groups. The first group included 20 participants with acute PNP without pleural complications; the second group included 21 children with acute PNP complicated by pyofibrinothorax. Results. Both groups were statistically comparable by age and gender (p > 0.05). At the same time, unlike the first group of patients who were admitted to the hospital on average 8.0 ± 3.4 days after the onset of a disease, children from the second group were usually admitted on average 10.4 ± 3.7 days after the onset of disease symptoms (p < 0.05), which, due to ineffective treatment on an outpatient basis, contributed to complications. The use of ultrasound in acute necrotizing pneumonia allowed for reduction of radiation exposure on the body of a child, dynamic monitoring of the focus of inflammation in the pleural cavity, control and influence on which increases the effectiveness of treatment that helped shorten length of stay in the hospital. Conclusions. Timely diagnosis of pleural complications in pneumonia and the choice of optimal strategy improve treatment outcomes in children with this pathology. The introduction to clinical practice of ultrasound monitoring of pleural cavities in children with acute necrotizing pneumonia, namely the appearance of the thickening of visceral and parietal pleura above 2.0–2.4 mm, allows for early detection of complications, specifying the diagnosis and treatment strategy, and prevention of destructive changes in the pleural cavity.